Sow Behavior Expression: Adoptions Effect - Arroyo, Paula (2018)
Crossed adoptions based on female potential are recommended in commercial production. This are made in the first 24 hours postpartum because it is at this moment that the imprinting occurs, it is the process by which certain stimuli are associated to produce different behaviors. In order to decrease or eliminate the recognition of the strange piglet, prior to introducing it into the new litter, different strategies are carried out. Early experiences may have long-term effects on future behavior. These experiences are influenced by mother-litter interaction. The aim of this work was to determine the possible association between adoptions and sows behavioral modifications. Females that donated piglets spent more time “walking” than those who did not donate piglets (p<0.05). And there is a possible relation between farrowing and the condition of being raised by an adoptive mother (p<0.05).